2018
DOI: 10.1097/sla.0000000000002353
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Resection for Colorectal Liver Metastases

Abstract: In patients undergoing parenchyma-sparing liver resection for colorectal metastases, laparoscopic surgery was associated with significantly less postoperative complications compared to open surgery. Laparoscopic resection was cost-effective compared to open resection with a 67% probability. The rate of free resection margins was the same in both groups. Our results support the continued implementation of laparoscopic liver resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
197
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 558 publications
(225 citation statements)
references
References 70 publications
9
197
3
3
Order By: Relevance
“…In most centers nowadays, laparoscopic surgery is considered standard of care for primary resectable colorectal cancer, and most recent consensus meetings on laparoscopic liver surgery have declared laparoscopy the standard for minor liver resections as well [2325]. In both procedures, a laparoscopic approach has been associated with faster recovery and shorter postoperative hospital stay, as well as decreased complication rates [21, 22, 26, 27]. Furthermore, the decreased need for pedicle clamping during laparoscopic liver surgery related to the intra-abdominal pressure during laparoscopy could decrease the risk of additional morbidity during LLCR [2832].…”
Section: Discussionmentioning
confidence: 99%
“…In most centers nowadays, laparoscopic surgery is considered standard of care for primary resectable colorectal cancer, and most recent consensus meetings on laparoscopic liver surgery have declared laparoscopy the standard for minor liver resections as well [2325]. In both procedures, a laparoscopic approach has been associated with faster recovery and shorter postoperative hospital stay, as well as decreased complication rates [21, 22, 26, 27]. Furthermore, the decreased need for pedicle clamping during laparoscopic liver surgery related to the intra-abdominal pressure during laparoscopy could decrease the risk of additional morbidity during LLCR [2832].…”
Section: Discussionmentioning
confidence: 99%
“…An obvious finding in the present study was that across the range of gastrointestinal cancer surgery a‐LOS was much longer than LOS reported in RCTs or single‐centre series4 5, 15. Seminal series have showed that open colectomy stays can be reduced to 2 days4, and laparoscopic surgery to just 23 h 5 .…”
Section: Discussionmentioning
confidence: 46%
“…Although these may have been intended as ‘proof of principle’, the present data showed a median a‐LOS of 8 days for open and 5 days for laparoscopic colonic resections. A recently published RCT15 comparing laparoscopic with open minor liver resections reported a median stay of 2 days after laparoscopy and 4 days following open surgery. The present study, with a median a‐LOS of 8 days after open and 3 days after laparoscopic resection for minor liver resections, is an interesting contrast, suggesting selection bias in a real‐world setting, but equally providing the impetus to improve perioperative care, particularly for those undergoing open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…While prospective, randomized data have not been required to promote MIS surgery in other domains, the recent Oslo CoMET study may help to promote MILR in this regard. 18 Regrettably, proper randomized prospective trials are costly and logistically prohibitive; therefore, we need to find other ways to address this shortfall to convince surgeons of the benefit MILR. There is a strong commitment from the MILR community to improve the quality of evidence and, combined with enhanced training and improvements in technology, to facilitate adoption.…”
mentioning
confidence: 99%